2020
DOI: 10.1073/pnas.2011674117
|View full text |Cite
|
Sign up to set email alerts
|

Social and behavioral consequences of mask policies during the COVID-19 pandemic

Abstract: Mandatory and voluntary mask policies may have yet unknown social and behavioral consequences related to the effectiveness of the measure, stigmatization, and perceived fairness. Serial cross-sectional data (April 14 to May 26, 2020) from nearly 7,000 German participants demonstrate that implementing a mandatory policy increased actual compliance despite moderate acceptance; mask wearing correlated positively with other protective behaviors. A preregistered experiment (n = 925) further indicates that a volunta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
183
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(195 citation statements)
references
References 15 publications
8
183
2
2
Order By: Relevance
“…For instance, Gostic and colleagues find that traveler screening was not particularly effective at containing the pandemic due to a large number of presymptomatic and asymptomatic travelers [36]. Facemask policies are also unlikely to help a country reach required thresholds of disease containment if the policies are loosely enforced and mask wearing remains a voluntary practice [37].…”
Section: Existing Researchmentioning
confidence: 99%
“…For instance, Gostic and colleagues find that traveler screening was not particularly effective at containing the pandemic due to a large number of presymptomatic and asymptomatic travelers [36]. Facemask policies are also unlikely to help a country reach required thresholds of disease containment if the policies are loosely enforced and mask wearing remains a voluntary practice [37].…”
Section: Existing Researchmentioning
confidence: 99%
“…Policymakers worldwide are increasingly seeking evidence-based policy instruments to combat the COVID-19 pandemic. While anecdotal evidence and laboratory experiments have shown the e cacy of mask-wearing in reducing infection chances, 4,5,15,16 the strength of the mandate's short and long-term effects relative to other NPIs has not been examined in observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Individual studies have assessed the e cacies of different NPIs. [1][2][3][4][5][6][7][8][9] Yet, despite their demonstrated effectiveness, many NPIs hurt the economy and other aspects of social and personal wellbeing. 7 Still, little is known about how NPIs compare in their relative e cacies.…”
Section: Introductionmentioning
confidence: 99%
“…One study with German participants demonstrated that mandating, rather than encouraging, mask use caused a higher level of compliance, with other protective behaviour correlated positively (53). It stated further that voluntary policy caused lower compliance of mask use and could intensify social stigma between people with and without masks (53).…”
Section: Behavioural Considerations Of Single-use and Reusable Masksmentioning
confidence: 99%
“…One study with German participants demonstrated that mandating, rather than encouraging, mask use caused a higher level of compliance, with other protective behaviour correlated positively (53). It stated further that voluntary policy caused lower compliance of mask use and could intensify social stigma between people with and without masks (53). An Italian study suggested that wearing masks causes people to comply with social distancing rules (54), adding to growing body of evidence of this effect (55), although there are no studies yet of the differences in these behaviours which correlate with single-use or reusable masks.…”
Section: Behavioural Considerations Of Single-use and Reusable Masksmentioning
confidence: 99%